Analisis Perbandingan Prediksi Kebangkrutan Model Altman dan Springate Pada Perusahaan Sub Sektor Konstruksi Bangunan - Fhebizarima Putri; Nafisah Nurulrahmatia; Puji Muniarty (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to determine whether there are differences in bankruptcy prediction result between the Altman model and the Springate model for building construction sub-sector companies listed on the Indonesia Stock Exchange. The type of research used comparative quantitative research. The population used is building construction sub-sector companies listed on the Indonesia Stock Exchange during the years 2018-2022. Sample collection uses purposive sampling technique. The analysis technique uses the Wilcoxon signed test. The Wilcoxon signed test indicate that the Altman and Springate models show significant difference in bankruptcy prediction result for building construction sub-sector companies listed on the Indonesia Stock Exchange.